(3eHGOF GdeMGSHI GdeGdjI(B(2) :s (3GdJShjGJ GdLQOjI hGdEaUGM GdeMGSHj (B/s - (3OQhjT, YHO GdfGUQ eMeO SjOs ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2010)
(3GdeYGLI GdeMGSHjI dLQO GdfbOjI(B- (3GdeYGdLI GdeMGSHjI dLQO GdeOjfhf(B- (3GdeYGdLI GdeMGSHjI dLQO ChQGb GdbHV hGddhGRe(B- (3GdeYGdLI GdeMGSHjI dLQO GdGSJKeGQGJ aj GdChQGb GdeGdjI bUjQI GdGLd(B- (3GdeYGdLI GdeMGSHjI dLQO eNRhf GdHVGYI(B- (3GdeYGdLI GdeMGSHjI dLQO GdGUhd GdKGHJI(B- (3GdeYGdLI GdeMGSHjI dLQO GdGUhd ZjQ GdedehSI hGdehGQO GdWHjYjI(B- (3GdeYGdLI GdeMGSHjI dLQO GdGdJRGeGJ hMbhb GdedcjI(B- (3GdbhGFe GdeGdjI(B.s
(3edGMb U(B.373 (3HjHdjhZQGajG(B:(3U(B.455s
Keywords: (3GdeGdjI GdYGeI(B- (3eMGSHIs; (3GdeMGSHI GdJMdjdjIs